Customer Satisfaction Of Luxury Hotels In Kish Island, Iran - Dolati, Somayeh (2011)
The purpose of this study is to study customer satisfaction in luxury hotel in Kish Island. There are three research objective in this research: 1. Identify the drivers and customer satisfaction results and also their relationship with customer satisfaction. 2. Identify customer satisfaction model for luxury hotel in Kish Island in Iran. 3. Determine whether there is a different between these two perspectives or not and what role does customer satisfaction factors have in making these differences,.